Analysis of Waste-Causing Factors Using the Lean Construction - Yosua Suryadarma Maleta; I Nyoman Dita Pahang Putra (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Islam Lamongan, 2026)
Building construction projects often face inefficiencies that lead to waste and disrupt project execution. Waste occurs when resources are expended without generating proportional value. This study aims to analyze the most important types of waste by applying the Lean Construction approach and analyzing the actions to handle them. Lean Construction classifies waste into seven categories: overproduction, inventory, defects, motion, transportation, waiting, and over-processing. A questionnaire was developed based on identified waste indicators, with responses analyzed using the Relative Importance Index (RII) to determine the most critical contributing factors. Further analysis of waste handling measures was conducted through a literature review, followed by a Focus Group Discussion (FGD) and decision-making using the Pareto method. The results of this study indicate that scattered materials in the project area, which obstruct the movement of other materials, are identified as the most critical factor contributing to waste. In addition, eight waste handling measures were identified based on the Pareto analysis.